Kinerja Aparatur Dalam Pelayanan Administrasi Kependudukan Di Kantor Kecamatan Kapala Pitu Kabupaten Toraja Utara - Viny Marsela Sombodatu; Nasir Mangasing (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research was conducted at the Kapala Pitu Sub-District Office, North Toraja Regency, with the aim of determining the "Performance of Apparatus in Civil Registration Administration Services at the Kapala Pitu Sub-District Office, North Toraja Regency". This study used a descriptive research type based on qualitative research. In qualitative research, informants were determined when the researcher entered the research area, totaling 5 individuals. Furthermore, data collection techniques in this study included Observation, Interviews, and Documentation. The required data consisted of primary and secondary data. The data analysis method involved Data Collection, Data Condensation, Data Presentation, and Drawing Conclusions. The theory used in this research was derived from Stephen Robins, which included 5 indicators: Work Quality, Work Quantity, Timeliness, Autonomy, and Effectiveness. The research findings revealed that the performance of the apparatus was not satisfactory, as there were still several aspects that needed improvement such as facilities and infrastructure, as well as enhancing Human Resources (HR), and conducting training to improve employee performance to become more productive, disciplined, and have good work ethics and attitudes.